Association of Mobile Instant Messaging Chat Group Participation With Family Functioning and Well-Being: Population-Based Cross-sectional Study - Zhao, Sheng Zhi; Luk, Tzu Tsun; Guo, Ningyuan; Wang, Man Ping; Lai, Agnes Yuen Kwan; Wong, Bonny Yee Man; Fong, Daniel Yee Tak; Chan, Sophia Siu Chee; Lam, Tai Hing (JMIR Publications, 2021)
BackgroundConvenient and quality family communication improves family functioning and well-being. Using mobile instant messaging (IM) for family communication is increasingly popular, but its association with family functioning and family well-being has not been reported. ObjectiveThe aim of this study was to examine the association of the use of family IM chat groups with family functioning and well-being, and the mediating effect of family communication quality among Chinese adults in Hong Kong. MethodsWe analyzed data from the Family and Health Information Trend Survey (FHInTS), a territory-wide, probability-based telephone survey conducted in 2017. The quality of family communication, family functioning, and well-being was assessed using the Family Communication Scale; Family Adaptation, Partnership, Growth, Affection, and Resolve (APGAR) Scale; and Family Well-Being Scale (family heath, harmony, and happiness), respectively. Respondents also reported the number of family IM chat groups (0, 1, 2, ≥3), and numbers of IM messages received (<1, 1-2, 3-10, 11-20, >20) and sent (<1, 1-2, 3-10, 11-20, >20) daily. The frequency of family IM chat interaction (range 0-8) was calculated by combining the number of messages received from and sent to the family IM chat groups daily. Covariates included sociodemographic characteristics and the frequency of family face-to-face communication (often, sometimes, seldom, or never). Data were weighted by sex, age, and education of the general population. Adjusted β coefficients of family functioning and well-being in relation to having a family IM chat group, and numbers of messages received and sent were calculated. The mediation effects of family communication on these associations were assessed, controlling for the covariates. ResultsA random sample of 1638 Chinese adults (45.6% men; 78.1% aged 25 to 64 years) were interviewed (response rate: 74.4%). Female, younger age, being married or cohabiting, higher education, higher income, better family functioning, and well-being were associated with having at least one family IM chat group (all P<.01). Higher scores of family communication, family APGAR, and family well-being were associated with having more family IM chat groups and more messages received from and sent to family IM chat groups daily (all P for trend <.01). More frequent family IM chat interaction was associated with higher scores of family communication, family APGAR, and family well-being (β=.16-.83, all P for trend <.001). The associations of family IM chat interaction with family functioning and well-being were moderately (51.0%-59.6%) mediated by family communication. ConclusionsUse of a family IM chat group was associated with higher family functioning and well-being, and the association was partially mediated by family communication.